A PROSPECTIVE STUDY OF ADVERSE DRUG REACTIONS DUE TO PLATINUM ANALOGS - CHEMOTHERAPY IN A TERTIARY CARE HOSPITAL - Kumar, Sumit; Badruddeen, Badruddeen; S P, Singh; Irfan Khan, Mohammad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to analyze the types of adverse drug reactions (ADRs) associated with platinum analogs (cisplatin, carboplatin and oxaliplatin) used for cancer chemotherapy in a tertiary care hospital and determine their causal relationship with the offending drug. Methods: This prospective, observational, non-interventional study was conducted in a tertiary care hospital at GSVM Medical College Kanpur, India, for 4 months. Patients of all age and either sex were included in the study. ADRs were reported by the physicians of oncology department of the hospital and ADRs were assessed for different parameters -causality, outcome, and seriousness of ADR as per the World Health Organization (WHO), type of ADRs as per expanded Rawlins and Thompson's classification, predictability using council for international organization of medical sciences guidelines and severity using modified Hartwig's scale. Descriptive statistics were used for data analysis. Results: A total of 140 ADRs were reported from platinum analogs following treatment of different types of cancer in hospital. The burden of ADRs in each patient was 2.41. Most of the ADRs were observed in the age group of 40–60 years. Vomiting (27 ADRs) was commonly reported reaction. Among platinum analogs, cisplatin leads to 82 ADRs (58.57%) followed by carboplatin with 53 ADRs (37.86%) and least with oxaliplatin 5 ADRs (3.57%). Most of the ADRs on causality assessment were possible (104, 74.29%) and probable (36, 25.71%) in nature. Type -A ADRs account for 4/5th of the total reported ADRs, followed by Type-B and C. Severity of 90.71% ADRs was found to be mild followed by moderate, with no case of severe and serious nature. Nearly, most of the ADRs were of predictable type (97.14%). Conclusion: The potential of platinum analogs to cause ADRs is high; thus, the need of effective ADRs monitoring is highly emphasized.